2009
DOI: 10.1080/01431160802545631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of satellite image spatial aggregation and resolution on estimates of forest land area

Abstract: Satellite imagery is being used increasingly in association with national forest inventories (NFIs) to produce maps and enhance estimates of forest attributes. We simulated several image spatial resolutions within sparsely and heavily forested study areas to assess resolution effects on estimates of forest land area, independent of other sensor characteristics. We spatially aggregated 30 m datasets to coarser spatial resolutions (90, 150, 210, 270, 510 and 990 m) and produced estimates of forest proportion fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 38 publications
(63 reference statements)
6
26
0
6
Order By: Relevance
“…For crown cover thresholds <1 differences in forest cover due to changes of the spatial resolution, simulated by spatial aggregation of pixels, were <10 %, an order of magnitude also reported by Nelson et al. (2009) for majority-based aggregation of Landsat images. The minor resolution effect can be highly relevant for remote sensing-based forest monitoring where information from sensors with different resolutions is combined.…”
Section: Discussionmentioning
confidence: 99%
“…For crown cover thresholds <1 differences in forest cover due to changes of the spatial resolution, simulated by spatial aggregation of pixels, were <10 %, an order of magnitude also reported by Nelson et al. (2009) for majority-based aggregation of Landsat images. The minor resolution effect can be highly relevant for remote sensing-based forest monitoring where information from sensors with different resolutions is combined.…”
Section: Discussionmentioning
confidence: 99%
“…A common experimental design for assessing scale effects in landscape ecology is to aggregate pixels or alter the thematic resolution of one or more land cover maps and quantify changes to response variables, such as landscape metric values [6,[58][59][60]. Another common multi-scale analysis method used frequently in landscape ecology characterises multiscale species-environment relationships by altering the size of circular buffers/kernel around point locations at which ecological data is sampled [61][62][63], while leaving the spatial or thematic resolution constant.…”
Section: Multi-scale Analysis Methodsmentioning
confidence: 99%
“…As other studies have shown the benefit of modeling FIA plot variables with a 3 × 3 (90 × 90 m) window (Healey, Lapoint, Moisen, & Powell, 2011), there is some justification for incorporating information from surrounding pixels into future strata map assignment procedures. Filtering may be one way to aggregate information and improve performance (Nelson, McRoberts, Holden, & Bauer, 2009) and thus will be a focus of future investigations.…”
Section: Design-based Forest Disturbance Estimatesmentioning
confidence: 99%